Assessing the Contribution of Smes Towards the Industrial Development of Ogun State - Segun Kehinde; Chinonye Moses; Borishade, Taiye; Kehinde, Oladele; Simon-ilogho, Busola; Obembe, Nifemi; Kemi Kehinde (International Journal of Integrated Science and Technology, 2023)
This study delves into the vital role played by Small and Medium-sized Enterprises (SMEs) in advancing the industrial development of Ogun State, Nigeria. SMEs are the backbone of the state's economic landscape, contributing significantly to employment, innovation, and economic growth. Through a comprehensive analysis of SMEs in various industries, this research evaluates their impact on industrial development. The assessment encompasses factors such as job creation, local value addition, and technology transfer, shedding light on the multifaceted contributions of SMEs. Additionally, the study explores the challenges faced by these enterprises and the potential for policy interventions to further enhance their role in industrial development. The findings of this research are invaluable for policymakers, business owners, and stakeholders aiming to bolster the industrial sector of Ogun State. By understanding the diverse ways in which SMEs contribute to industrial development, strategic decisions and policies can be formulated to foster sustainable growth and economic prosperity in the state.